Analysis of Islamic Criminal Law on the Acquittal of Khalwat Perpetrators : (Study Of Verdict Number 21/JN/2023/MS. Bna and Number 22/JN/2023/MS. Bna) - Ibnu Zarir; Abd. Mukhsin (Lambung Mangkurat Law Journal, 2025)
This study aims to evaluate the mindset of the Banda Aceh MS Panel of Judges in deciding the case of acquittal against the defendant in the khalwat case, as stipulated in Qanun Aceh Number 6 of 2014. The method used is a normative juridical approach with case studies on two decisions, namely Decision Number 21/JN/2023/MS. Bna and Number 22/JN/2023/MS. Bna. The findings in this study show that the Panel of Judges adheres to the principle of In Dubio Pro Reo, the principle of Unus Testis Nullus Testis, as well as the principles of Tabayyun and Tasabbut. However, the application of the principle of Unus Testis Nullus Testis is considered inappropriate, because although the Assembly stated that there was only one witness, in fact the Public Prosecutor presented three witnesses. In addition, the application of the principle of In Dubio Pro Reo gives the impression that there are doubts from the Panel of Judges in assessing the case, even though based on the facts of the trial, the element of intentionality is not clearly and decisively proven. Thus, the use of such principles is considered irrelevant. The element of intentionality and the existence of two valid pieces of evidence cannot be proven, so the indictment is declared not to meet the requirements of proof according to the law..